Transatrial stenting for long‐term management of cardiac tumor obstruction of the right atrium in 3 dogs. (18th December 2020) - Weisse, Chick; Scansen, Brian A.; Berent, Allyson C.; Cober, Rick E.
Abstract: Background: Venous obstruction in dogs caused by large intracardiac masses can result in severe morbidity with few safe treatments. Hypothesis/Objectives: Retrospective study to report results after transatrial stent placement in dogs with naturally occurring cardiac masses causing venous obstruction. Animals: Three client‐owned dogs diagnosed with large cardiac masses. Methods: Retrospective study of patients that received transatrial stents extending from the caudal vena cava, across the right atrium, and into the cranial vena cava (CrVC). Procedures, complications, and outcomes were recorded based upon medical records, referring veterinarians, and client communications. Results: Two dogs had similar clinical signs suggestive of congestive hepatopathy including marked ascites and lethargy. One dog had clinical signs of CrVC syndrome including head and neck swelling with pitting edema and pleural effusion. After stent placement, venous pressure gradients were decreased and repeat angiography confirmed that vascular patency was reestablished. Resolution of clinical signs was marked in all 3 dogs with only mild complications including tachyarrhythmias and hypertension in 1 dog during the perioperative period. Two dogs that required additional transatrial stent placement for reobstruction 6 and 14 months later improved after the second stent implantation. Survival times poststenting for the dogs were 3, 21, and 37 months, with cause of death related to the cardiac tumor in all dogs. Conclusions and Clinical Importance: Endovascular transatrial stenting may provide a long‐term palliative treatment option for dogs with clinical signs attributable to tumor‐induced venous obstruction when more traditional treatments are declined or not indicated.